Efficient and stable propylene selective superposition catalyst and preparation method thereof
By using a catalyst composed of layered hydrotalcite and metal oxide promoters, and forming a coated core-shell structure through surface modification, the problem of insufficient stability of propylene selective stacked catalysts and product isomerization in the existing technology is solved. problem, achieving efficient, stable and economical propylene selective superposition reaction.
Patent Information
- Application Number
- CN202411672922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, propylene selective superposition catalysts have problems such as insufficient stability and serious isomerization of selective superposition products, which leads to difficult and poor economical continuous operation of the process.
Adopt a catalyst composed of layer -like water talcium main layer structure, metal oxide auxiliary agent, and covered nuclear shell structures that are composed of two -price and three -valent metal cations and layers. Catalyst catalyst.
An efficient and stable propylene selective superposition reaction is achieved, with high olefin selective superposition activity, stability and regeneration performance. The product has low branching degree and the process economy is improved.
Smart Images

Figure CN119346183A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to an efficient and stable propylene selective superposition catalyst and a preparation method thereof. Background Art
[0002] Propylene is an important chemical raw material, mainly used in the production of polypropylene, acrylonitrile, propylene oxide, cumene (phenol / acetone), oxo alcohol (butyl / octanol), acrylic acid and isopropanol, etc. Other uses include alkylation oil, catalytic selective superposition and dimerization, etc. It is an important petrochemical basic raw material second only to ethylene. my country first produced propylene through the oil route, namely steam cracking and catalytic cracking. In recent years, new processes such as coal chemical industry, propane dehydrogenation, and C4 olefin disproportionation, such as methanol to olefins (MTO) and methanol to propylene (MTP), have become increasingly mature. For example, the propylene produced by dozens of domestic companies such as CNOOC Shell, Shenhua Ningmei, Wanhua Chemical, Zhongtian Hechuang, SECCO, Qilu Petrochemical, Yangzi Petrochemical, and Shanghai Petrochemical has a total production capacity of more than 40 million tons / year, resulting in the consumption of propylene gradually falling behind the growing production of propylene monomer. Therefore, the development of efficient and stable processes to convert propylene into high-value-added chemical intermediates is an urgent need and a challenging opportunity facing the chemical industry.
[0003] Heterogeneous catalytic selective superposition of propylene is one of the most promising pathways, which can produce a series of chemical products, such as dimer 4-methyl-1-pentene, which can be used to synthesize high-performance polyolefins, linear hexene, which can be used as a high-octane gasoline blending component, and can also be used to prepare hexyl alcohol as a gold ore emulsifier; trimer nonene can be used to prepare nonionic surfactants, and tetramer dodecene can be used as lubricant additives, plasticizers, etc. The propylene selective superposition process that occupies a monopoly abroad is the solid phosphoric acid catalyst used in the SPAC process developed by UOP in the United States, which is prepared by loading phosphoric acid with diatomaceous earth as a carrier, as reported in patents US4097365 and US4738767. On this basis, Shanghai Petrochemical Research Institute in China added boric acid to stabilize the skeleton structure and developed T-49 and T-99 catalysts, as reported in patents CN1078663A and CN1285241A. Solid phosphoric acid catalysts are used industrially to achieve selective superposition of propylene at a temperature of 150°C to 200°C and a pressure of 4 to 5 MPa, with a single-pass conversion rate of 40% to 80%. However, this type of catalyst has the fatal disadvantage of being easy to become muddy and easy to agglomerate, and the process is difficult to operate continuously. It is necessary to strictly control the injection of water during the reaction to extend the operating life, but the maximum extension is half a year and the catalyst is deactivated and cannot be regenerated. In addition, the process product has a large degree of olefin cracking, a wide carbon number distribution, and poor economic efficiency. Compared with traditional solid phosphoric acid catalysts, molecular sieves, aluminosilicates and activated carbon are used to synthesize solid phosphoric acid catalysts, as reported in patent US5051386, but this catalyst cannot fundamentally change its shortcomings. Solid acid catalysts also have good activity in the preparation of high-value-added high-carbon olefin products by polymerization of low-carbon olefins. The MOGD process developed by Mobil is a representative example. With HZSM-25 pore zeolite molecular sieve as catalyst and Al2O3 as co-catalyst, about 80% of diesel components are obtained under the reaction conditions of T=190-310°C and p=4-10MPa. Alumina or alumina / silicon oxide is used as a carrier to support metal sulfate salts, as reported in patents US3959400, CN1193552A, and CN1077452C. The propylene conversion rate is above 90%, and the sum of the selectivity of the selective superposition products nonene and dodecene is about 70%. However, there is also a catalyst with strong acidity, which leads to cracking and isomerization of the selective superposition products, and the carbon number distribution is wide, which cannot meet the requirement of low branching degree of the desired olefin oligomers.
[0004] Layered metal hydroxides (LDHs) are ordered assemblies of metal cations and interlayer anions with a two-dimensional structure, and have many excellent properties, such as adjustable denaturation, adsorption, memory effect, topological invariance, and surface acidity and alkalinity. They have great potential applications in heterogeneous catalysis. By adjusting their unique physical and chemical properties, including microstructure, surface / interface defect structure, and surface acid / base sites, they become important carrier materials, especially in the construction of bifunctional or multifunctional heterogeneous catalysts.
[0005] In summary, the main problems of the heterogeneous catalytic selective polymerization of propylene are insufficient catalyst stability and severe isomerization of the selective polymerization olefin products. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a highly efficient and stable propylene selective superposition catalyst which is simple to prepare and can be regenerated and reused.
[0007] Another technical problem to be solved by the present invention is to provide a method for preparing the highly efficient and stable propylene selective superposition catalyst.
[0008] To solve the above problems, the present invention discloses a highly efficient and stable propylene selective superposition catalyst, characterized in that the catalyst is composed of a layered hydrotalcite main body plate structure including divalent and trivalent metal cations and interlayer anion intercalation, a metal oxide additive and a coated core-shell structure.
[0009] The divalent and trivalent metal cations are two or more of Ni, Fe, Co, Cu, Mg, and Al, and the molar ratio of the divalent to trivalent cations is 1:4 to 4:1.
[0010] The metal oxide additive is one or more of ZrO2, TiO2, ZnO2, SiO2, CaO and MgO, and its content is 5% to 20% of the catalyst mass.
[0011] The method for preparing the highly efficient and stable propylene selective superposition catalyst as described above is characterized in that: the method refers to compounding a layered hydrotalcite main layer plate structure with adjustable active components with a metal oxide additive, and then performing surface modification on it to obtain a coated core-shell structure catalyst.
[0012] The method for preparing the highly efficient and stable propylene selective superposition catalyst as described above comprises the following steps:
[0013] ⑴ Prepare a nitrate aqueous solution or carbonate aqueous solution of divalent and trivalent metal cations and an alkaline solution of anions respectively, wherein the molar concentration of the metal cations in the salt solution is 0.1% to 1%, and the molar concentration of the anions in the alkaline solution is 0.5% to 5%; then prepare a layered hydrotalcite by a coprecipitation method using the nitrate aqueous solution or carbonate aqueous solution and the alkaline solution, which is recorded as N-LDHs, where N is the metal cation;
[0014] (2) Add a metal oxide additive to the layered hydrotalcite, age it in an oil bath at 50°C to 80°C for 12h to 24h, then filter it, wash it with deionized water 4 to 8 times, and then filter it. The filter cake is dried at 70°C to 110°C for 12h to 24h to obtain N-LDHs / MO x ;
[0015] ⑶ Prepare N-LDHs / MO x After grinding and sieving, precursor powder particles with a particle size greater than 100 meshes are obtained. The precursor powder particles are impregnated with the dissolved surface modifier by a step-by-step impregnation method; after the impregnation, the precursor powder particles are stirred evenly, first placed in an oven at 70°C to 110°C for 12h to 24h, and then placed in a calcining furnace at 400°C to 600°C for 4h to 8h under an inert atmosphere to obtain a catalyst N-LDHs / MO with a coated core-shell structure. x @Modifier.
[0016] The alkaline solution in step (1) is an aqueous solution of sodium hydroxide and sodium carbonate mixed in any volume ratio.
[0017] In the step (3), the surface modifier is a C or / and N modifier and a Si or / and Al modifier; the C or / and N modifier is one or more of melamine, polyethylene glycol, sucrose, glucose, mannitol, and sorbitol, and the addition amount thereof is 0.5% to 3% of the catalyst, and is dissolved in deionized water; the Si or / and Al modifier is one or more of ethyl orthosilicate, methyl orthosilicate, aluminum isopropoxide, and aluminum sec-butoxide, and the addition amount thereof is 1% to 5% of the catalyst mass, and is dissolved in alcohol.
[0018] The use of the catalyst in the process of preparing C6, C9, and C12 olefins is characterized in that the catalyst is contacted with a propylene raw material in a fixed bed reactor for a selective superposition reaction, and the contact conditions include: a temperature of 80 to 150° C., a pressure of 2.0 to 5.0 MPa, and a raw material liquid mass space velocity of 0.1 to 5.0 h -1 .
[0019] The mass fraction of olefins in the propylene raw material is greater than 99%.
[0020] The propylene raw material contains less than 1 ppm of nitrogen compounds, less than 5 ppm of sulfides, and less than 20 ppm of oxygen-containing compounds.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] The catalyst provided by the present invention has a layered hydrotalcite main body plate structure with adjustable active components, provides a special reaction channel for the reactant propylene molecule, reasonably regulates the distribution of active components and acid sites, and obtains a coated core-shell structure catalyst through surface modification, which has high olefin selective superposition activity, good stability and regeneration performance, and the preparation method is simple and low in cost. The obtained selective superposition olefin product has a low degree of branching. Experiments show that within the process conditions provided by the present invention, a propylene conversion rate of 85% to 65% is achieved, wherein the C6 olefin selectivity is 45% to 60%, the C9 olefin selectivity is 20% to 30%, and the C12 olefin selectivity is 10% to 20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0024] Figure 1 The catalyst provided in Example 1 of the present invention.
[0025] Figure 2 This is the XRD characterization diagram of the catalyst provided in Example 1 of the present invention.
[0026] Figure 3 This is a TEM characterization image of the catalyst provided in Example 1 of the present invention.
[0027] Figure 4 This is the NH3-TPD characterization diagram of the catalyst provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] A highly efficient and stable propylene selective superposition catalyst comprises a layered hydrotalcite main body plate structure including divalent and trivalent metal cations and interlayer anion intercalation, a metal oxide auxiliary agent and a coated core-shell structure.
[0029] Wherein: the divalent and trivalent metal cations are two or more of Ni, Fe, Co, Cu, Mg, and Al, and the molar ratio of the divalent to trivalent cations is 1:4 to 4:1.
[0030] The metal oxide additive is one or more of ZrO2, TiO2, ZnO2, SiO2, CaO and MgO, and its content is 5% to 20% of the catalyst mass.
[0031] A method for preparing an efficient and stable propylene selective superposition catalyst comprises compounding a layered hydrotalcite main plate structure with adjustable active components with a metal oxide additive and then performing surface modification to obtain a coated core-shell structure catalyst.
[0032] The specific process is as follows:
[0033] ⑴ Prepare divalent and trivalent metal cation nitrate aqueous solution or carbonate aqueous solution, anion alkaline solution, wherein the molar concentration of metal cations in the salt solution is 0.1% to 1%, and the molar concentration of anions in the alkaline solution is 0.5% to 5%; then prepare layered hydrotalcite by coprecipitation of the nitrate aqueous solution or carbonate aqueous solution and the alkaline solution, which is recorded as N-LDHs, where N is the metal cation.
[0034] The alkaline solution is a water solution of sodium hydroxide and sodium carbonate mixed in any volume ratio. The pH value of the solution is maintained at 7 to 10 during the preparation process.
[0035] (2) Add metal oxide additives to the layered hydrotalcite, age it in an oil bath at 50°C to 80°C for 12h to 24h, then filter it and wash it with deionized water 4 to 8 times, and then dry the filter cake at 70°C to 110°C for 12h to 24h to obtain N-LDHs / MO x .
[0036] ⑶ Prepare N-LDHs / MO x After grinding with a mortar and then screening, grinding and screening are performed to obtain precursor powder particles with a particle size greater than 100 meshes, and the precursor powder particles are impregnated with the dissolved surface modifier by a step-by-step impregnation method. The surface modifier is a C or / and N modifier and a Si or / and Al modifier; the C or / and N modifier is one or more of melamine, polyethylene glycol, sucrose, glucose, mannitol, and sorbitol, and the addition amount is 0.5% to 3% of the catalyst, and it is dissolved in deionized water; the Si or / and Al modifier is one or more of ethyl orthosilicate, methyl orthosilicate, aluminum isopropoxide, and aluminum sec-butoxide, and the addition amount is 1% to 5% of the catalyst mass, and it is dissolved in alcohol.
[0037] After the impregnation, the mixture was stirred evenly in a crucible, first placed in an oven at 70°C to 110°C for 12h to 24h, and then placed in a calcination furnace and calcined at 400°C to 600°C for 4h to 8h under an inert atmosphere to obtain a core-shell structured catalyst N-LDHs / MO. x @Modifier.
[0038] Application of the above catalyst in the process of preparing C6, C9 and C12 olefins: the catalyst is contacted with propylene raw material in a fixed bed reactor for selective superposition reaction, and the contact conditions include: temperature of 80-150°C, pressure of 2.0-5.0 MPa, and raw material liquid mass space velocity of 0.1-5.0 h -1 , preferably: temperature is 80-110°C, pressure is 2.0-3.0 MPa, and mass space velocity of raw material liquid is 0.4-2.0h -1 .
[0039] Wherein: the mass fraction of olefins in the propylene raw material is greater than 99%.
[0040] The nitrogen compounds (basic or non-basic nitrogen compounds) in the propylene raw material are less than 1 ppm, the sulfides (such as sulfides, hydrosulfides, carbonyl sulfides) are less than 5 ppm, and the oxygen-containing compounds (such as water, alcohols, ketones, ethers, etc.) are less than 20 ppm.
[0041] The main products generated by the selective polymerization of propylene in the present invention are C6, C9 and C12 olefin products, and C6, C9 and C12 with a purity of more than 99% are obtained respectively by vacuum distillation, and the obtained selective polymerization olefin products are hydrogenated to alkanes to determine the components of the selective polymerization olefin products.
[0042]
[0043] Example 1
[0044] (1) Weigh 77.86 g of Ni(NO3)2·6H20, 8.42 g of Ca(NO3)2·4H20, 15.9 g of Mg(NO3)2·6H20, and 55.2 g of Al(NO3)3·9H20, and dissolve them in 680 ml of deionized water to obtain a metal salt solution. Weigh 40.0 g of NaOH and 21.2 g of Na2CO3, and dissolve them in 200 ml of deionized water to obtain an alkaline solution. A 1000ml three-necked flask was placed in an oil bath and salt solution and alkaline solution were added dropwise. The pH of the mixed solution was kept at about 9 under constant stirring. After the addition was completed, 40g of 30% silica sol was weighed and 15g of 30% titanium sol was weighed. The mixture was added to the three-necked flask and stirred for 0.5h. The oil bath temperature was increased to 80°C and allowed to stand for aging for 24h before being filtered and washed 4 times with deionized water. The filter cake was dried at 100°C for 24h to obtain NiCa-LDHs / SiO2-TiO2.
[0045] (2) After grinding the prepared NiCa-LDHs / SiO2-TiO2 in a mortar, weigh 20.0 g of particles larger than 100 mesh and place them in a crucible, dissolve 2.0 g of melamine in 10 g of deionized water, dissolve 0.5 g of aluminum sec-butoxide in 5 g of sec-butanol, and dissolve 0.5 g of tetraethyl orthosilicate in 5 g of anhydrous ethanol. Slowly add the catalyst powder, stir evenly in the crucible, place in an oven and dry at 100 °C for 24 h, then place in a calcining furnace and calcine at 500 °C for 3 h in a nitrogen atmosphere to obtain a C, N, Si, Al modified NiCa-LDHs / SiO2-TiO2@CNSiAl catalyst, such as Figure 1 shown.
[0046] The crystal structure of the catalyst in Example 1 is characterized as follows: Figure 2 As shown, the main diffraction peak is TiO2. At the same time, the particle dispersion is characterized, such as Figure 3 As shown, the metal particles are evenly dispersed.
[0047] The acidity of the catalyst in Example 1 was characterized as follows: Figure 4 As shown, it indicates that the catalyst has certain weak acid sites and medium-strong acid sites.
[0048] The solid particles were compressed in a tablet press at a pressure of 10 MPa, and then ground and sieved, and the particles with a mesh size of 20-40 were taken for catalytic performance evaluation.
[0049] The catalyst is used for the selective polymerization reaction of propylene at a reaction temperature of 80°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 0.8 h -1 The reaction was carried out under the conditions of , and after running for 24 hours, the liquid product was collected in a wide-mouth bottle and the product composition was analyzed by gas chromatography; the analysis showed that the propylene conversion rate was 88.6%, the C6 product selectivity was 57.2%, the C9 product selectivity was 28.1%, and the C12 product selectivity was 11.5%.
[0050] Example 2
[0051] (1) Weigh 43.70 g of Ni(NO3)2·6H20, 3.82 g of Mg(NO3)2·6H20, and 19.05 g of Al(NO3)3·9H20, and dissolve them in 680 ml of deionized water to obtain a metal salt solution. Weigh 40.0 g of NaOH and 21.2 g of Na2CO3, and dissolve them in 200 ml of deionized water to obtain an alkaline solution. Place a 1000 ml three-necked flask in an oil bath and drip the salt solution and the alkaline solution at the same time. Keep the pH of the mixed solution at about 10 under constant stirring. After the dripping is completed, weigh 5.0 g of ZrO2 and add it to the three-necked flask, stir for 0.5 h, then increase the oil bath temperature to 70°C, stand for aging for 24 h, and then filter and wash with deionized water 4 times. The filter cake is dried at 100°C for 24 h to obtain Ni-LDHs / ZrO2.
[0052] (2) After grinding the prepared Ni-LDHs / ZrO2 in a mortar, weigh 20.0 g of particles larger than 100 mesh and place them in a crucible, dissolve 1.0 g of mannitol in 10 g of deionized water, dissolve 0.5 g of methyl orthosilicate in 10 g of anhydrous methanol, slowly add the catalyst powder step by step, stir evenly in the crucible, place in an oven at 100°C to dry for 24 h, then place in a calcining furnace and calcine at 400°C for 6 h under a nitrogen atmosphere to obtain C, Si modified Ni-LDHs / ZrO2@CSi catalyst. The solid particles are pressed in a tablet press at a pressure of 10 MPa, and then ground and sieved, and 20-40 mesh particles are taken for catalytic performance evaluation.
[0053] The catalyst is used for the selective polymerization reaction of propylene at a reaction temperature of 100°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 0.8 h -1 The reaction was carried out under the conditions of , and after running for 24 hours, the liquid product was collected in a wide-mouth bottle and the product composition was analyzed by gas chromatography; the analysis showed that the propylene conversion rate was 52.4%, the C6 product selectivity was 47.6%, the C9 product selectivity was 27.2%, and the C12 product selectivity was 17.6%.
[0054] Example 3
[0055] (1) Weigh 40.87 g of Ni(NO3)2·6H20, 5.45 g of Co(NO3)3·6H20, 3.82 g of Mg(NO3)2·6H20, and 19.05 g of Al(NO3)3·9H20, and dissolve them in 680 ml of deionized water to obtain a metal salt solution. Weigh 40.0 g of NaOH and 21.2 g of Na2CO3, and dissolve them in 200 ml of deionized water to obtain an alkaline solution. Place a 1000 ml three-necked flask in an oil bath and drip the salt solution and the alkaline solution at the same time. Keep the pH of the mixed solution at about 9 under constant stirring. After the dripping is completed, weigh 5.0 g of TiO2 and add it to the three-necked flask, stir for 0.5 h, then increase the oil bath temperature to 80°C, stand for aging for 24 h, and then filter and wash with deionized water 4 times. The filter cake is dried at 100°C for 24 h to obtain NiCo-LDHs / TiO2.
[0056] (2) After grinding the prepared NiCo-LDHs / TiO2 in a mortar, weigh 20.0g of particles larger than 100 mesh and place them in a crucible. Dissolve 1.5g of glucose in 10g of deionized water and 0.5g of aluminum isopropoxide in 10g of isopropanol. Then slowly add the catalyst powder step by step, stir evenly in the crucible, place in an oven and dry at 100°C for 24h, then place in a calcining furnace and calcine at 500°C for 3h under a nitrogen atmosphere to obtain C, Al modified NiCo-LDHs / TiO2@CAl catalyst. The solid particles are pressed in a tablet press at a pressure of 10MPa, and then ground and sieved. Take the particles with a mesh size of 20-40 for catalytic performance evaluation.
[0057] The catalyst is used for the selective polymerization reaction of propylene at a reaction temperature of 90°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 0.4 h -1 The reaction was carried out under the conditions of , and after running for 24 hours, the liquid product was collected in a wide-mouth bottle and the product composition was analyzed by gas chromatography; the analysis showed that the propylene conversion rate was 68.4%, the C6 product selectivity was 65.2%, the C9 product selectivity was 21.2%, and the C12 product selectivity was 10.5%.
[0058] Example 4
[0059] (1) Weigh 39.06 g of Ni(NO3)2·6H20, 18.1 g of Fe(NO3)3·9H2O, 3.82 g of Mg(NO3)2·6H20, and 19.05 g of Al(NO3)3·9H20, and dissolve them in 680 ml of deionized water to obtain a metal salt solution. Weigh 40.0 g of NaOH and 21.2 g of Na2CO3, and dissolve them in 200 ml of deionized water to obtain an alkaline solution. A 1000ml three-necked flask was placed in an oil bath and salt solution and alkaline solution were added dropwise. The pH of the mixed solution was kept at about 9 under constant stirring. After the addition was completed, 15g of 30% mass fraction titanium sol was weighed and 1.5g of SiO2 was weighed and added to the three-necked flask at the same time. After stirring for 0.5h, the oil bath temperature was increased to 80°C and allowed to stand for aging for 24h. After suction filtering, it was washed 4 times with deionized water. The filter cake was dried at 100°C for 24h to obtain NiFe-LDHs / TiO2-SiO2.
[0060] (2) After grinding the prepared NiFe-LDHs / TiO2-SiO2 in a mortar, weigh 20.0 g of particles larger than 100 mesh and place them in a crucible. Dissolve 2.0 g of polyethylene glycol in 10 g of deionized water and 0.8 g of aluminum sec-butoxide in 10 g of sec-butanol. Slowly add the catalyst powder step by step, stir evenly in the crucible, place in an oven and dry at 100°C for 24 h, then place in a calcining furnace and calcine at 550°C for 3 h under a nitrogen atmosphere to obtain C, Al modified NiFe-LDHs / TiO2-SiO2@CAl catalyst. Press the solid particles in a tablet press at a pressure of 10 MPa, grind and sieve after tableting, and take 20-40 mesh particles for catalytic performance evaluation.
[0061] The catalyst is used for the selective polymerization reaction of propylene at a reaction temperature of 90°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 1.2 h -1 The reaction was carried out under the conditions of , and after running for 24 hours, the liquid product was collected in a wide-mouth bottle and the product composition was analyzed by gas chromatography; the analysis showed that the propylene conversion rate was 76.3%, the C6 product selectivity was 58.6%, the C9 product selectivity was 28.2%, and the C12 product selectivity was 10.7%.
[0062] Example 5
[0063] (1) Weigh 77.86 g of Ni(NO3)2·6H20, 15.2 g of Cu(NO3)2·3H2O, 15.9 g of Mg(NO3)2·6H20, and 55.2 g of Al(NO3)3·9H20, and dissolve them in 680 ml of deionized water to obtain a metal salt solution. Weigh 40.0 g of NaOH and 21.2 g of Na2CO3, and dissolve them in 200 ml of deionized water to obtain an alkaline solution. A 1000ml three-necked flask was placed in an oil bath and salt solution and alkaline solution were added dropwise. The pH of the mixed solution was kept at about 9 under continuous stirring. After the addition was completed, 35g of silica sol with a mass fraction of 30% was weighed, and 2.5g of CaO was weighed and added to the three-necked flask at the same time. After stirring for 0.5h, the oil bath temperature was increased to 80°C, and the mixture was aged for 24h before being filtered and washed with deionized water 4 times. The filter cake was dried at 100°C for 24h to obtain NiCu-LDHs / SiO2-CaO.
[0064] (2) After grinding the prepared NiCu-LDHs / SiO2-CaO in a mortar, weigh 20.0 g of particles larger than 100 mesh and place them in a crucible, dissolve 2.0 g of melamine in 10 g of deionized water, dissolve 0.5 g of tetraethyl orthosilicate in 10 g of anhydrous ethanol, slowly add the catalyst powder, stir evenly in the crucible, place in an oven and dry at 100°C for 24 h, then place in a calcining furnace and calcine at 550°C for 3 h under a nitrogen atmosphere to obtain C, N, Si modified NiCu-LDHs / SiO2-CaO@CNSi catalyst. The solid particles are pressed in a tablet press at a pressure of 10 MPa, and after pressing, they are ground and sieved, and 20-40 mesh particles are taken for catalytic performance evaluation.
[0065] The catalyst is used for the selective polymerization reaction of propylene at a reaction temperature of 110°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 0.8 h -1 The reaction was carried out under the conditions of , and after running for 24 hours, the liquid product was collected in a wide-mouth bottle and the product composition was analyzed by gas chromatography; the analysis showed that the propylene conversion rate was 78.2%, the C6 product selectivity was 53.2%, the C9 product selectivity was 30.1%, and the C12 product selectivity was 14.4%.
[0066] Comparative Example 1
[0067] The NiCa-LDHs / SiO2-TiO2 precursor was prepared according to the method of Example 1, except that it was not modified by the surface modifier, and the catalyst was used for the evaluation of the propylene selective superposition reaction under the same conditions as in Example 1. The analysis showed that the propylene conversion rate was 53.8%, the C6 product selectivity was 54.4%, the C9 product selectivity was 30.8%, and the C12 product selectivity was 11.6%.
[0068] Comparative Example 2
[0069] The Ni-LDHs / ZrO2 precursor was prepared according to the method of Example 2, except that it was not modified by the surface modifier, and the catalyst was used for the evaluation of the propylene selective superposition reaction under the same conditions as in Example 2. The analysis showed that the propylene conversion rate was 41.3%, the C6 product selectivity was 58.2%, the C9 product selectivity was 28.6%, and the C12 product selectivity was 10.5%.
[0070] Comparative Example 3
[0071] The NiCo-LDHs / TiO2 precursor was prepared according to the method of Example 3, except that it was not modified by the surface modifier, and the catalyst was used for the evaluation of the propylene selective superposition reaction under the same conditions as in Example 3. The analysis showed that the propylene conversion rate was 46.5%, the C6 product selectivity was 52.6%, the C9 product selectivity was 28.4%, and the C12 product selectivity was 17.1%.
[0072] Comparative Example 4
[0073] NiFe-LDHs / TiO2-SiO2 was prepared according to the method of Example 4, except that it was not modified by a surface modifier, and the catalyst was used for the evaluation of the propylene selective superposition reaction under the same conditions as in Example 4. Analysis showed that the propylene conversion rate was 68.9%, the C6 product selectivity was 55.4%, the C9 product selectivity was 25.4%, and the C12 product selectivity was 16.8%.
[0074] Comparative Example 5
[0075] NiCu-LDHs / SiO2-CaO was prepared according to the method of Example 5, except that it was not modified by a surface modifier, and the catalyst was used for propylene selective superposition reaction evaluation under the same conditions as in Example 5. Analysis showed that the propylene conversion rate was 64.7%, the C6 product selectivity was 59.7%, the C9 product selectivity was 21.2%, and the C12 product selectivity was 11.2%.
[0076] Embodiments 6 to 9
[0077] This example illustrates the catalytic reaction effect of the catalyst of the present invention with different contents of the surface modification additive.
[0078] The same catalyst preparation method as in Example 1 was used to prepare catalysts with different surface modifier contents for the selective polymerization reaction of propylene. The reaction conditions were the same as in Example 1. The results are listed in Table 1.
[0079] Table 1
[0080] Surface modifier content % Propylene conversion rate / % C6 olefin selectivity % C9 olefin selectivity % C12 olefin selectivity / % 0.5 62.5 52.9 30.2 16.7 1.0 71.3 54.1 28.6 14.6 3.0 78.3 50.6 32.3 12.4 5.0 51.3 58.2 24.5 10.9
[0081] It can be seen from Table 1 that different surface modification additive contents affect the catalytic reaction effect of the catalyst of the present invention.
[0082] Embodiments 10 to 13
[0083] This example illustrates the process conditions applicable to the present invention: the raw material mass space velocity (WHSV) is 0.4-2.0h -1 .
[0084] The catalyst in Example 1 was used for propylene selective polymerization reaction by changing the mass space velocity of the raw material and keeping the reaction temperature and pressure unchanged. The results are listed in Table 2.
[0085] Table 2:
[0086]
[0087] Embodiment 14
[0088] The catalyst in Example 1 was used at a reaction temperature of 80°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 0.8 h-1 The reaction was run for 1000 h under the conditions of , and the results are shown in Table 3.
[0089] Table 3
[0090]
[0091] It can be seen from Table 3 that the catalyst provided by the present invention has good stability in the propylene selective polymerization reaction.
[0092] Embodiment 15
[0093] The catalyst of Example 14 was subjected to in-situ calcination. After the catalyst of Example 14 was operated for 1000 hours, the introduction of propylene raw material was stopped, air was introduced at a flow rate of 100 ml / min, the temperature was raised to 500° C., and calcination was performed for 6 hours. Then, the catalyst was operated for 500 hours under the same conditions as Example 14, and the average conversion rate of propylene was above 75%. This experiment shows that the catalyst of the present invention has good regeneration performance.
[0094] Example 16
[0095] The catalyst in Example 1 was used at a reaction temperature of 80°C, a reaction pressure of 3.0 MPa, and a liquid hourly space velocity of 0.8 h -1 The reaction was run under the conditions of , and the obtained olefin products were subjected to vacuum distillation to obtain C6, C9, and C12 olefins with a purity greater than 99%. The C6 product after distillation was hydrogenated in a high-pressure reactor using a Ni-based catalyst to obtain the C6 olefin component distribution. The results are shown in Table 4.
[0096] Table 4
[0097] C6 component Selectivity / % Methylpentene 50.4 Hexene 49.6 Degree of branching 0.504
[0098] It can be seen from Table 4 that the olefin product obtained in the propylene selective polymerization reaction using the catalyst provided by the present invention has a low degree of branching.
Claims
1. A highly efficient and stable propylene selective superposition catalyst, characterized in that: The catalyst consists of a layered hydrotalcite main body layer plate structure including divalent and trivalent metal cations and interlayer anion intercalation, a metal oxide auxiliary agent and a coated core-shell structure.
2. The highly efficient and stable propylene selective superposition catalyst according to claim 1, characterized in that: The divalent and trivalent metal cations are two or more of Ni, Fe, Co, Cu, Mg, and Al, and the molar ratio of the divalent to trivalent cations is 1:4 to 4:
1.
3. The highly efficient and stable propylene selective superposition catalyst according to claim 1, characterized in that: The metal oxide additive is one or more of ZrO2, TiO2, ZnO2, SiO2, CaO, and MgO, and its content is 5% to 20% of the catalyst mass.
4. The method for preparing a highly efficient and stable propylene selective superposition catalyst according to any one of claims 1 to 3, characterized in that: The method is to compound a layered hydrotalcite main plate structure with adjustable active components with a metal oxide additive, and then perform surface modification on it to obtain a coated core-shell structure catalyst.
5. The method for preparing the highly efficient and stable propylene selective superposition catalyst according to claim 4, comprising the following steps: ⑴ Prepare divalent and trivalent metal cation nitrate aqueous solution or carbonate aqueous solution and anion alkaline solution respectively, and the molar concentration of metal cation in the salt solution is 0.1%~1%, and the molar concentration of anion in the alkaline solution is 0.5%~5%; then prepare layered hydrotalcite by coprecipitation of nitrate aqueous solution or carbonate aqueous solution and alkaline solution, recorded as N-LDHs, where N is metal cation; (2) Add a metal oxide additive to the layered hydrotalcite, age it in an oil bath at 50°C to 80°C for 12h to 24h, then filter it, wash it with deionized water 4 to 8 times, and then filter it. The filter cake is dried at 70°C to 110°C for 12h to 24h to obtain N-LDHs / MO x ; ⑶ Prepare N-LDHs / MO x After grinding and sieving, precursor powder particles with a particle size greater than 100 mesh are obtained. The precursor powder particles are impregnated with the dissolved surface modifier by a step-by-step impregnation method. After the impregnation, the precursor powder particles are stirred evenly, first placed in an oven at 70°C to 110°C for 12h to 24h, and then placed in a calcining furnace at 400°C to 600°C for 4h to 8h under an inert atmosphere to obtain a catalyst N-LDHs / MO coated with a core-shell structure. x @Modifier.
6. The method for preparing the highly efficient and stable propylene selective superposition catalyst according to claim 5, characterized in that: The alkaline solution in step (1) is an aqueous solution of sodium hydroxide and sodium carbonate mixed in any volume ratio.
7. The method for preparing a highly efficient and stable propylene selective superposition catalyst according to claim 5, characterized in that: In the step (3), the surface modifier is a C or / and N modifier and a Si or / and Al modifier; the C or / and N modifier is one or more of melamine, polyethylene glycol, sucrose, glucose, mannitol, and sorbitol, and its addition amount is 0.5% to 3% of the catalyst, and it is dissolved in deionized water; the Si or / and Al modifier is one or more of tetraethyl orthosilicate, methyl orthosilicate, aluminum isopropoxide, and aluminum sec-butoxide, and its addition amount is 1% to 5% of the catalyst mass, and it is dissolved in alcohol.
8. The use of the catalyst according to any one of claims 1 to 3 in the process for preparing C6, C9, C12 olefins, characterized in that: The catalyst is contacted with propylene raw material in a fixed bed reactor for selective superposition reaction. The contact conditions include: temperature of 80-150°C, pressure of 2.0-5.0 MPa, and raw material liquid mass space velocity of 0.1-5.0 h -1 .
9. Use of the catalyst as claimed in claim 8 in the process of preparing C6, C9, C12 olefins, characterized in that: The mass fraction of olefins in the propylene raw material is greater than 99%.
10. Use of the catalyst according to claim 9 in the process of preparing C6, C9, C12 olefins, characterized in that: The propylene raw material contains less than 1 ppm of nitrogen compounds, less than 5 ppm of sulfides, and less than 20 ppm of oxygen-containing compounds.
Citation Information
Patent Citations
Olefin oligomerization catalyst, process for preparing the same, and olefin oligomerization process using the same
CN1077452C
Solid catalyst for olefin copolymerisation
CN1078663A
Solid ziegler catalyst for olefins and preparation thereof
CN1193552A
Propene oligomerization solid phosphoric acid catalyst
CN1285241A
Hydrocracking process and catalyst for production of middle distillate oils
US4097365A